Physical properties, storage stability, and consumer acceptability for sourdough bread produced using encapsulated kombucha sourdough starter culture - Mohd Roby, Bizura Hasida; Muhialdin, Belal J.; Mahmood Taleb Abadl, Muna; Mat Nor, Nor Arifah; Marzlan, Anis Asyila; Abdul Halim Lim, Sarina; Mustapha, Nor Afizah; Meor Hussin, Anis Shobirin (Wiley, 2020)
This study aimed to produce sourdough bread using an encapsulated kombucha sourdough starter culture without the addition of baker's yeast. The bioactive metabolites of kombucha sourdough starter and sourdough starter without kombucha were identified using 1H-NMR analysis with multivariate analysis. The physical properties, including loaf volume, specific loaf volume, firmness, and water activity were determined following standard methods. The shelf life and consumer acceptability of the bread were also being evaluated. The principal component analyses showed the presence of 15 metabolites in kombucha sourdough starter. The major compounds that contributed to the differences from sourdough starter without kombucha were alpha-aminobutyric acid, alanine, acetic acid, riboflavin, pyridoxine, anserine, tryptophan, gluconic acid, and trehalose. The encapsulated kombucha sourdough starter increased the loaf volume (976.7 ± 25.2 mL) and specific loaf volume (4.38 ± 0.12 mL/g) compared to yeast bread. Thus, significant (P < 0.05) reduction was observed in the crumb firmness (116.07 ± 6.28 g) compared to traditional sourdough bread and yeast bread. The encapsulated kombucha sourdough starter extended the shelf life of bread by 5 to 10 days at room temperature. The sourdough bread prepared using the encapsulated kombucha sourdough starter demonstrated significantly (P < 0.05) higher taste and overall acceptability scores compared to the other bread. The findings indicate that the encapsulated kombucha sourdough starter is promising to produce functional sourdough bread with extended shelf life and improved quality.